Innovation in Bioremediation of Acid Mine Drainage using Hybrid Tara (Caesalpinia spinosa) and Sawdust Biofilters, Michiquillay, 2025 - Licapa-Redolfo, Gladys S; Poma De La Cruz, Paulo Cesar; Collazos Sanchez, Jackelini; Saldaña Chavez, Renzo Alessandro (LACCEI, 2025)
In this study, the efficacy of a tara shell and sawdust biofilter in removing Cu, Zn, and Fe from acid mine drainage (AMD) (initial pH 3.66–3.74) was evaluated. The influence of contact time (0, 30, 60, 120, and 180 min) and relative material dosage (82.5/82.5 g and 41.25/123.75 g of sawdust/tara; total 165 g in 1.5 L) on the results was investigated. The tests were carried out in triplicate (n = 3) and the concentrations were determined by atomic absorption and subsequently the removal percentages were calculated at 180 min, Cu reached 96.60%, 97.01% and 99.94% (minimum Cf = 0.018 mg / L), while Fe achieved 95.60% and 67.12% in the evaluated dates; Zn showed moderate efficiencies of 24.89%, 49.26% and 12.93%, conditioning the selectivity Cu > Fe > Zn. The optimal combination for Cu with 180 min and 41.25 / 123.75 g of biomass ratio, evidence that the increase in time improves the removal to a point close to equilibrium. It is concluded that the tara-sawdust biofilter is a low-cost and highly effective alternative to reduce Cu and Fe in AMD, requiring pH and proportion adjustments to maximize Zn capture.